A corpus analysis of cohesion in World Health Organization speeches by the Director General on Covid-19 vaccination - Mika Nakajima; Kam-Fong Lee; Mansour Amini (Training, Language and Culture, 2023)
Although cohesion and coherence of a speech are significant, and there is an array of studies exploring these elements, particularly political speeches, many still struggle to apply the correct grammar and lexical cohesion as well the correct thematic structure in speech construction. This study aims to investigate the cohesion and coherence of speeches that are constructed through textual metafunction using thematic structures and cohesive devices. The study intends to answer two research questions. 1. What are the thematic structures and cohesive devices used in the speeches delivered by the Director General of the World Health Organization? 2. How are these thematic structures and cohesive devices used to produce cohesion in these speeches? This study used a mixed-method approach, combining corpus analysis with qualitative descriptive analysis. Twelve speeches from the website of the World Health Organization were chosen using a purposive sampling method. Thematic patterns and the distribution of cohesive devices in the speech corpus were analysed and identified. Findings showed that unmarked topical themes were employed the most, whereas interpersonal themes were used the least. The most dominant cohesive device was repetition, followed by reference, conjunction, and collocation. Ellipsis was sparsely employed to avoid redundancy. These mechanisms contributed to constructing cohesion and coherence, which help audiences understand the speeches better. The findings of the study may have significant implications for enhancing communication across a range of fields by offering useful insights on the efficacy of utilising cohesive devices and thematic structures in speeches, particularly those delivered by prominent public figures.